(untitled) (Zaporizhzhia Historical Review, 2021)
This article is on forms and methods of getting acquainted with historical past of Zaporizhzhya region, with the organization of mass excursions to new industrial buildings as well as on taking part in the work of science field-works, popular-scientific organizations and the like